DiGeorge‐like syndrome in a child with a 3p12.3 deletion involving MIR4273 gene born to a mother with gestational diabetes mellitus. Issue 7 (24th April 2017) - Cirillo, Emilia; Giardino, Giuliana; Gallo, Vera; Galasso, Giovanni; Romano, Roberta; D'Assante, Roberta; Scalia, Giulia; Del Vecchio, Luigi; Nitsch, Lucio; Genesio, Rita; Pignata, Claudio
Abstract : Chromosome 22q11.2 deletion is the most common chromosomal alteration associated with DiGeorge syndrome (DGS), even though this is not the only underlying cause of DGS. In rare patients, mutations in a single gene, TBX1, have been described resulting in a DGS phenotype. Recently, it has been reported that at least part of the TBX1 mutant phenotype is due to excessive bone morphogenetic proteins (BMP) signaling. Evidence suggests that miRNA may modulate the expression of critical T‐box transcriptional regulators during midface development and Bmp‐signaling. We report on a 7‐year‐old Caucasian male born to a mother affected with gestational diabetes (GDM) who had a 371Kb‐interstitial deletion of 3p12.3 identified by array CGH, involving the ZNF717, MIR1243, and 4273 genes. The child presented with a DiGeorge anomaly (DGA) associated with unilateral renal agenesis and language delay. The immunological evaluation revealed a severe reduction and impairment of T lymphocytes. FISH analysis and TBX1 sequencing were negative. Among the miRNA‐4273 predicted target genes, we found BMP3, which is involved in several steps of embryogenesis including kidney and lung organogenesis and in insulin gene expression. Since, DGA is not commonly found in newborns of diabetic mothers, we hypothesize that the pathogenesis of DGA associated with GDM is multifactorial, involving both genetic and/or epigenetic cofactors.